2024
DOI: 10.1039/d3nj04431a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro retardation and modulation of human insulin amyloid fibrillation by Fe3+ and Cu2+ ions

Swarnali Paul,
Shahnaz Begum,
Hasan Parvej
et al.

Abstract: Metal ions of the later part of the first-row transition series (Fe, Co, Ni, Cu, and Zn) can form bonds through the carboxylate, hydroxyl, thiol, and imidazole side chains of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…24,25 For example, Fe(III)-and Ni(II)-based complexes have shown inhibitory effect on insulin fibrillation. 25,26 Insulin hormone is an important supplement for type II diabetic patients; 27 however, there is also a growing concern regarding the amyloid related health risks due to insulin aggregation in the syringe vials and formation of amyloid structures at the site of repeated insulin injection. 28,29 The imbalance in the level of Cu(II) ions causes diabetic-linked complications, and studies have confirmed increased diabetic cases due to Cu(II) deficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 For example, Fe(III)-and Ni(II)-based complexes have shown inhibitory effect on insulin fibrillation. 25,26 Insulin hormone is an important supplement for type II diabetic patients; 27 however, there is also a growing concern regarding the amyloid related health risks due to insulin aggregation in the syringe vials and formation of amyloid structures at the site of repeated insulin injection. 28,29 The imbalance in the level of Cu(II) ions causes diabetic-linked complications, and studies have confirmed increased diabetic cases due to Cu(II) deficiency.…”
mentioning
confidence: 99%
“…Hence, in this study, we examined the antiamyloid effect of Cu(II) on insulin. Recent studies have indicated that different metal ions have shown their affinity for insulin which can influence the conformational and aggregation properties of insulin. , For example, Fe(III)- and Ni(II)-based complexes have shown inhibitory effect on insulin fibrillation. , Insulin hormone is an important supplement for type II diabetic patients; however, there is also a growing concern regarding the amyloid related health risks due to insulin aggregation in the syringe vials and formation of amyloid structures at the site of repeated insulin injection. , The imbalance in the level of Cu(II) ions causes diabetic-linked complications, and studies have confirmed increased diabetic cases due to Cu(II) deficiency. , …”
mentioning
confidence: 99%